2019
DOI: 10.3389/fnmol.2019.00294
|View full text |Cite
|
Sign up to set email alerts
|

The Alpha Isoform of Heat Shock Protein 90 and the Co-chaperones p23 and Cdc37 Promote Opioid Anti-nociception in the Brain

Abstract: Opioid activation of the mu opioid receptor (MOR) promotes signaling cascades that evoke both analgesic responses to pain and side effects like addiction and dependence. Manipulation of these cascades, such as by biased agonism, has great promise to improve opioid therapy. However, the signaling cascades of the MOR are in general poorly understood, providing few targets for drug development. In our earlier work, we identified Heat shock protein 90 (Hsp90) as a novel and crucial regulator of opioid anti-nocicep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…However, these hypotheses only address the slower tolerance seen over time with repeated treatment, they do not explain the tolerance rescue we observed. One potential clue for this rescue mechanism could be our earlier findings that both brain and spinal cord effects of Hsp90 inhibition on anti-nociception require rapid protein translation [1416]. The translation inhibitor we used had no impact on anti-nociception in Vehicle-treated mice, suggesting that this mechanism is newly activated upon Hsp90 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, these hypotheses only address the slower tolerance seen over time with repeated treatment, they do not explain the tolerance rescue we observed. One potential clue for this rescue mechanism could be our earlier findings that both brain and spinal cord effects of Hsp90 inhibition on anti-nociception require rapid protein translation [1416]. The translation inhibitor we used had no impact on anti-nociception in Vehicle-treated mice, suggesting that this mechanism is newly activated upon Hsp90 inhibitor treatment.…”
Section: Discussionmentioning
confidence: 98%
“…One potential avenue is to investigate specific Hsp90 isoforms and co-chaperones active in the spinal cord. In our earlier work, we found that the Hsp90α isoform and the co-chaperones p23 and Cdc37 were responsible for regulating anti-nociception in the brain [22]. If different isoforms and/or co-chaperones regulate opioid antinociception in the spinal cord, then we could use isoform-and co-chaperone-selective inhibitors to selectively inhibit spinal cord Hsp90 even with systemic administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another reason may be related to the activity of Hsp90 inhibitors on pain drugs, such as opioids. Previous studies showed that inhibition of Hsp90 in the mouse brain could diminish the opioid-induced signaling and behavior [ 29 , 30 ]. The increased risk of pain by Hsp90 inhibitors could relate to the attenuation of pain management in the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The Hsp90 chaperone family contains four isoforms in mammalian cells. These isoforms are Hsp90α, Hsp90β, glucose response protein 94 (Grp94), and tumor necrosis factor type 1 receptor-associated protein (TRAP1) [6]. Hsp90α/β operates in the cytosol while Grp94 localizes to the endoplasmic reticulum and TRAP1 to the inner mitochondrial space [7].…”
Section: Introduction 1hsp90 As a Chaperonementioning
confidence: 99%